2003
DOI: 10.1021/ac0258913
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Based Statistical Scorer for Tandem Mass Spectrometry

Abstract: We describe a new statistical scorer for tandem mass spectrometry. The scorer is based on the probability that fragments with given chemical properties create measured intensity levels in the experimental spectrum. The scorer's parameters are computed using a fully automated procedure. Benchmarking the new scorer on a large set of experimental spectra, we show that it performs significantly better than the widely used cross-correlation scoring algorithm of Eng et al. (Eng, J. K; McKormack, A. L.; Yates, J. R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 22 publications
2
135
1
Order By: Relevance
“…The very high percentage of spectra correctly assigned by Prospector in this study (over two-thirds) is in contrast to most previously published dataset of high throughput ion trap data where between 5 and 15% of the acquired spectra could be interpreted (2,3,26), although one study has reported 40% identification (25). This is unlikely to be a reflection of the reliability of results searched with different search engines but rather a measure of the relative quality of data acquired on a QqTOF instrument in comparison to that acquired on an ion trap both in terms of mass accuracy and the presence of a full mass range in the fragmentation spectra.…”
Section: Figcontrasting
confidence: 93%
“…The very high percentage of spectra correctly assigned by Prospector in this study (over two-thirds) is in contrast to most previously published dataset of high throughput ion trap data where between 5 and 15% of the acquired spectra could be interpreted (2,3,26), although one study has reported 40% identification (25). This is unlikely to be a reflection of the reliability of results searched with different search engines but rather a measure of the relative quality of data acquired on a QqTOF instrument in comparison to that acquired on an ion trap both in terms of mass accuracy and the presence of a full mass range in the fragmentation spectra.…”
Section: Figcontrasting
confidence: 93%
“…A number of algorithms and scoring models have been developed to assess the likelihood of a match. They can show different selectivity and sensitivity at the edge of good spectral quality, and some programs have enough flexibility to permit the use of different types of MS/ MS data or modification patterns 6,7,[40][41][42][43][44][45][46][47][48][49][50][51][52][53] . Four basic approaches have been developed to model matches to sequences: descriptive, interpretative, stochastic and probability-based modeling (Box 2).…”
Section: Review Of Database Search Algorithmsmentioning
confidence: 99%
“…Statistical and probability models for database searching This group of methods uses models based on empirically generated fragment ion probabilities 45,48,51 . In these methods no a priori determined probabilities are used.…”
Section: Box 3 Strategy For Large Scale Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since collision-activated dissociation (CAD) was performed by an LTQ mass spectrometer we expect to find the typical abundant fragments such as y-and b-peaks and their derivatives [9,36,37,16]. However, with FT-ICR it is possible to detect rare ion-fragments, which could not be identified with lower resolution instruments since they would be indistinguishable from noise (see for example analysis on similar data with low resolution instruments [38]).…”
Section: Fourier Transform Mass Spectrometry and Peptide Fragmentationmentioning
confidence: 99%